The Genomic Complexity of a Large Inversion in Great Tits - da Silva, Vinicius H (Genome Biol Evol, 2019)
Chromosome inversions have clear effects on genome evolution and have been associated with speciation, adaptation, and the evolution of the sex chromosomes. In birds, these inversions may play an important role in hybridization of species and disassortative mating. We identified a large ([Formula: see text] 64 Mb) inversion polymorphism in the great tit (Parus major) that encompasses almost 1,000 genes and more than 90% of Chromosome 1A. The inversion occurs at a low frequency in a set of over 2,300 genotyped great tits in the Netherlands with only 5% of the birds being heterozygous for the inversion. In an additional analysis of 29 resequenced birds from across Europe, we found two heterozygotes. The likely inversion breakpoints show considerable genomic complexity, including multiple copy number variable segments. We identified different haplotypes for the inversion, which differ in the degree of recombination in the center of the chromosome. Overall, this remarkable genetic variant is widespread among distinct great tit populations and future studies of the inversion haplotype, including how it affects the fitness of carriers, may help to understand the mechanisms that maintain it.